Reduced plasma carotenoids in individuals suffering from metabolic diseases with disturbances in lipid metabolism: a systematic review and meta-analysis of observational studies. (3rd October 2021) - Iqbal, Wasim A.; Mendes, Ines; Finney, Kieran; Oxley, Anthony; Lietz, Georg
Abstract: This review summarises the association between serum carotenoids, serum retinoids and dietary intake outcomes with obesity/overweight and individuals with metabolic diseases with disturbances in lipid metabolism. Observational studies reporting dietary intakes and serum concentrations of carotenoids and retinol were collected from Medline and Web of Science. Mean differences were calculated between "cases" (classified as obese, overweight or having a metabolic disease with disturbances in lipid metabolism; i.e. non-alcoholic fatty liver disease, type 2 diabetes, dyslipidaemia or metabolic syndrome) and "comparator group" (classified as normal weight healthy individuals) and summarised in meta-analyses. Significant summary measures were observed for most serum provitamin A and non-provitamin A carotenoids. Studies reporting total serum carotenoids had shown the greatest decrease (–0.28 µmol/l [–0.33, −0.23], p <.001, I 2 =62.5%, n = 7). There were no significant summary measures for dietary outcomes, suggesting a physiological role of low serum carotenoids in the development of obesity and associated diseases.